2016
DOI: 10.17795/zjrms-7557
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in Pregnancy: Presentation, Management and Complications

Abstract: Background: Diagnosis of acute appendicitis in pregnancy is difficult. Delay operation, increase complications. Objectives: This study focused on early operation on base of careful history, precise physical examination, and rational close observation and evaluates its results with conventional investigation in pregnant women suspected acute appendicitis. Materials and Methods: A cross sectional study in100 pregnant women and 100 aged matched non pregnant women underwent appendectomy during Sep 2011 -Dec 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Similar to what has been reported in the literature, most of our patients were in the second trimester [ 13 ]. However, Davoodabadi et al [ 14 ] found that the incidence of acute appendicitis during pregnancy was high during the third trimester. The second trimester is considered as the most appropriate time for appendectomy and this period has the lowest risk for fetus from operation and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to what has been reported in the literature, most of our patients were in the second trimester [ 13 ]. However, Davoodabadi et al [ 14 ] found that the incidence of acute appendicitis during pregnancy was high during the third trimester. The second trimester is considered as the most appropriate time for appendectomy and this period has the lowest risk for fetus from operation and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In the second month of gestation, the neutrophil count starts to increase and plateaus in the second or third trimester. During that time the total leucocyte counts range from 10000 to 15,000/mm 3 [ 14 ]. The current study reported 62.5% of abnormal leukocyte count which is in concordance with what was reported by Hiersch et al [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To decrease negative appendectomy, and postoperative complication "accurate and timely diagnosis are needed" 15,25 and perforated appendicitis in most of the patients 26 , is a result of delayed consultation, additional ultrasonography or CT scan of the abdomen can be performed in order not to operate hastily, albeit it is recommended to monitor changes in symptoms a little longer 27 , with retaking precise symptoms and signs catlike observation of 12 ± 8 hours could be sufficient to make surgical decisions, "Despite a high negative appendectomy" 17,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature review of the 14 published studies (n=98.933) comparing pregnant (n=3.971) and non-pregnant AAp (n=94.962) reveal that NA rates of pregnant women vary from 0% to 38% whereas NA rates of non-pregnant women vary from 0% to 21.8%. [4,5,[9][10][11][12][13][14][15][16][17][18][19][20] In eight of these studies, NA was found to be higher in pregnant patients, whereas in three of these studies, NA was found to be higher in non-pregnant. Although it was not statistically significant, NA rates of pregnants were higher in the study we present (26.0 vs. 20.8%).…”
Section: Discussionmentioning
confidence: 99%